(untitled) (Revista horizonte, 2021)
The present research work addresses the gross motor development in boys and girls belonging to the field field hockey branch of the Club Deportivo Alemán de Concepción Octava Región-Chile. The main objective of the research is to describe the effects of a program based on recreational-motor activities on the level of gross motor development of children belonging to the Lawn Hockey School of the Club Deportivo Alemán with the application of the TGMD-2 test used as the main instrument for the elaboration of the research. The results obtained by means of the gross motor development test showed that 50% of the sample was in the category "At age", 20% of the sample was in the category "Under age", 20% "Over age" and 10% in the category "Above age", results obtained in the pre-test, after the intervention that included 26 sessions focused on recreational motor activities, The post-test was applied, which indicated that the sample improved the level of gross motor development, placing 20% "At age", 20% "Over age", 50% in the "Superior" category and 10% in the "Very superior" category. The children evaluated presented an improvement in the level of gross motor development equivalent to their age, placing them in better post-intervention categories.